Dermatophilus congolensis. IV. Maintenance of laboratory strains - Cruz, Luiz Celso Hygino da (Pesquisa Agropecuaria Brasileira, 2014)
Strains of Dermatophilus congolensis were maintained in our laboratory for more than two and a half years. The strains were kept in semi-solid Brain-heart infusion agar (0.8% agar). The tubes were kept at room temperature, closed with white rubber stoppers. No detectable change of morphological and physiological properties occurred during this period. The same strains did not survive for more than 16 months at 4°C on scabs from which they originally had been isolated.